2008
DOI: 10.1017/s0033291708002912
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse inhibition of the startle reflex depends on the catecholO-methyltransferase Val158Met gene polymorphism

Abstract: These results suggest that PPI is regulated by DA neurotransmission in the PFC and its levels depend on the COMT Val158Met gene polymorphism. These findings enhance the value of the PPI paradigm in examining individual variability of early information processing in healthy subjects and psychiatric disorders associated with changes in PFC DA activity and attentional deficits such as schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
3
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 70 publications
(103 reference statements)
7
72
3
5
Order By: Relevance
“…PPI levels predict gray matter availability in frontal cortical areas in patients with schizophrenia (Kumari et al, 2008), which extends to the hippocampal, striatal, thalamic, and temporal regions in healthy subjects (Kumari et al, 2005). Consistent with these neuroimaging findings and the notion that sensorimotor gating is important in human cognition (Geyer et al, 1990), neuropsychological studies show that higher PPI levels predict superior performance on tasks that rely on the integrity and efficiency of PFC function Bitsios et al, 2006;Giakoumaki et al, 2006;Csomor et al, 2008).We have recently shown that COMT Val158 allele loading is associated with lower PPI levels in healthy men (Roussos et al, 2008a). We proposed that this may be due to low PFC DA transmission and increased prefrontal noise in Valloading subjects and/or that the Val158 allele may indirectly increase striatal dopaminergic function, thus reducing PPI, likely as downstream manifestation of reduction in cortical information processing.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…PPI levels predict gray matter availability in frontal cortical areas in patients with schizophrenia (Kumari et al, 2008), which extends to the hippocampal, striatal, thalamic, and temporal regions in healthy subjects (Kumari et al, 2005). Consistent with these neuroimaging findings and the notion that sensorimotor gating is important in human cognition (Geyer et al, 1990), neuropsychological studies show that higher PPI levels predict superior performance on tasks that rely on the integrity and efficiency of PFC function Bitsios et al, 2006;Giakoumaki et al, 2006;Csomor et al, 2008).We have recently shown that COMT Val158 allele loading is associated with lower PPI levels in healthy men (Roussos et al, 2008a). We proposed that this may be due to low PFC DA transmission and increased prefrontal noise in Valloading subjects and/or that the Val158 allele may indirectly increase striatal dopaminergic function, thus reducing PPI, likely as downstream manifestation of reduction in cortical information processing.…”
mentioning
confidence: 57%
“…We proposed that this may be due to low PFC DA transmission and increased prefrontal noise in Valloading subjects and/or that the Val158 allele may indirectly increase striatal dopaminergic function, thus reducing PPI, likely as downstream manifestation of reduction in cortical information processing. In any case, PFC DA transmission seems to be an important neural mechanism that modulates human PPI (Roussos et al, 2008a). The aim of the present study was to better understand the relationship among COMT, PPI, and executive function.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, strains of both mice and rats have been identified with relatively low basal PPI levels, and investigators have also taken the strategy of identifying "low gating" rats within a particular strain, and in both cases, these strains and substrains have been shown to be more sensitive to PPI-enhancing effects of drugs or brain stimulation (Acheson et al 2012;Angelov et al 2014;Swerdlow et al 2006). Roussos et al (2008) reported parallel findings in humans, in which healthy subjects homozygous for the Val allele of the rs4680 COMT polymorphism exhibited low basal PPI levels and PPI-enhancing effects of the COMT inhibitor, tolcapone, while individuals homozygous for the MET allele of rs4680 exhibited high basal PPI and PPI-reducing effects of tolcapone. There are also rat strain differences in the sensitivity to PPI-enhancing versus disruptive effects of the same drugs, even among commonly used outbred rat strains (e.g., Swerdlow et al 2004), that are independent of basal PPI levels, and are associated with the differential expression of several genes, including COMT, within PPI-regulatory circuitry (Shilling et al 2008).…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 99%
“…The PPI deficit in schizophrenia is supposed to reflect a central abnormality underlying the disease; both neuroanatomical and neurochemical factors have been implicated on the basis of animal studies, which suggest contributions of diverse neurotransmitter systems, and particular functional association with multiple loci in the cortico-striato-pallido-thalamic (CSPT) circuitry, frontal and mediotemporal regions, ventral striatum, ventral pallidum, and pontine regions of the brainstem [12,37]. Furthermore, PPI is heritable [2,16], decreased in unaffected relatives of schizophrenia patients [7,19], affected by SNPs within the dopamine, acetylcholine, and serotonin system [24,[29][30][31]34] and already reduced during the prodromal stage of schizophrenia [28,39], suggesting that PPI is an important and valid candidate as an intermediate or endophenotypic marker in genetic studies of schizophrenia [14].…”
Section: Tcf4 and Sensorimotor Gatingmentioning
confidence: 99%